SISTEM ZONASI DI KOTA PADANG PANJANG - Pratama, Yogha; Ernawati, Ernawati (JURNAL BUANA, 2023)
This study aims to find out: (1) How is the zoning system policy in the city of Padang Panjang, and (2) What are the obstacles that arise with the implementation of the zoning system in accepting students in the city of Padang Panjang. This research uses a qualitative research type with a descriptive analysis approach for data collection using non-participatory observation techniques, interviews, and documentation, informant selection techniques using Snowball Sampling, as well as for data analysis from data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) The zoning system policy is in the form of abolishing SKTM (Certificate of Disadvantage), length of domicile, announcement of capacity, and priority of one zoning of school of origin. because the admissions system focuses on prospective educators who live in the closest distance to one of the schools. The implementation of a policy of limiting the capacity of schools that makes prospective students who have good abilities or high scores does not guarantee getting the school they want, so there is fraud at the domicile address with the address on the family card (KK) in order to get the desired school for prospective students. (2) Constraints on the zoning system in the form of implementation techniques that are not socialized to the community, the availability of schools is not evenly distributed, the priority of distance causes decreased motivation, the dichotomy of superior and non-excellent schools. Limited time for socialization which ultimately affects people's understanding of the new mechanism for accepting new students after the zoning policy was enacted through Permendikbud 17 of 2017.